2020
DOI: 10.1002/htj.21976
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on controlled cooling by coupling of thermoelectric and an air impinging jet for CPU

Abstract: In this study, experimental tests have been carried out on the coupling thermoelectric cooling module with minichannel heatsink subjected to impinging airflow for cooling desktop central processing unit (CPU). A controlled thermoelectric‐forced test system was designed for this purpose. This was designed using electronic Arduino card. The proposed hybrid cooling system was compared with the conventional forced air‐cooling technique. Three power of heat source (CPU) were adopted, investigated, and compared, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Termoelektrik soğutucular, elektronik yongaların soğutulmasında, çalışma kimyasalları içermemeleri , uygulama yönteminin kolay ve ekonomik olması nedeniyle tercih edilmektedir [14]. Bir termoelektrik modüle verilen elektrik akımı ve üzerinden geçen havanın hızı arttıkça soğutma performansı artmaktadır [15]. Genel olarak, bu sonuçlar bir kontrol metodolojisinin hem araştırma hem de endüstriyel uygulamalarda faydalı olabileceğini göstermektedir [16] Tasarım ve uygulamayı kolaylaştırmak için algoritmalardan oluşan derin öğrenme modelleriyle daha iyi tahminler yapılabilmektedir [17].…”
Section: Figure a Graphic Design Of The Systemunclassified
“…Termoelektrik soğutucular, elektronik yongaların soğutulmasında, çalışma kimyasalları içermemeleri , uygulama yönteminin kolay ve ekonomik olması nedeniyle tercih edilmektedir [14]. Bir termoelektrik modüle verilen elektrik akımı ve üzerinden geçen havanın hızı arttıkça soğutma performansı artmaktadır [15]. Genel olarak, bu sonuçlar bir kontrol metodolojisinin hem araştırma hem de endüstriyel uygulamalarda faydalı olabileceğini göstermektedir [16] Tasarım ve uygulamayı kolaylaştırmak için algoritmalardan oluşan derin öğrenme modelleriyle daha iyi tahminler yapılabilmektedir [17].…”
Section: Figure a Graphic Design Of The Systemunclassified
“…TEG efficiency is influenced by different factors, including: (i) thermoelectric properties of the material in terms of thermal conductivity K, Seebeck coefficient α, and resistivity ρ, (ii) temperature gradient, which is affected by the sink and source capacities and heat transfer rate, (iii) the figure of merit (ZT) which is a non-dimensional metric that represents TEG overall performance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Their test results showed that this system improved the cooling performance by 64.8% in relation to the traditional air-cooling. Lin et al [62] combined a TE module with a microchannel heat sink filled with TiO2 nanofluid that was successful in cooling an LED substrate below 53.1 • C when it was subjected to an ambient temperature of 65 • C. Belarbi et al [63] reported that combining air-jet impingement cooling with TE cooling improved the CPU cooling performance by 15%. Based on a thin-film TE module, Kattan et al [64] suggested a form of on-demand cooling solution for the mobile chip.…”
Section: Introductionmentioning
confidence: 99%